Points-of-differences that shape consumer preferences for a hype brand: The case of Mixue’s fast growth - Christopher, Anthony; Simamora, Bilson (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2023)
Companies position their brands to consumers using points of difference, attributes, or advantages that consumers strongly associate with the brand and cannot be found in competing brands. Mixue is an ice cream brand that enjoyed significant attention in early 2023. The question is, why did this ice cream outlet receive spectacular attention in such a short time? To answer this question, based on the theory of consumer behavior models that asserts that a company's marketing efforts influence consumer decision-making, the authors theorize that the intentionally created point of difference (PODs) boost consumer preferences. To confirm that applied theory, the authors collected data from 136 respondents who have visited Mixue outlets by distributing questionnaires via Google Forms. The partial least square (PLS), with the help of WarpPLS 7.0 and SPSS 26, reveals that intrinsic and extrinsic product attributes positively and significantly impact consumer preferences. However, these controllable variables only account for 32% of consumer preference and 68% of unidentified non-POD factors. The challenge for the company in maintaining success in the long term is to enhance its uniqueness by increasing the contribution of the PODs. Other researchers are suggested to investigate non-POD factors.